2021
DOI: 10.3390/ijms22020876
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Compounds from Glycyrrhiza uralensis as Therapeutic Agents for the Muscle Disorders

Abstract: Skeletal muscle is the most abundant tissue and constitutes about 40% of total body mass. Herein, we report that crude water extract (CWE) of G. uralensis enhanced myoblast proliferation and differentiation. Pretreatment of mice with the CWE of G. uralensis prior to cardiotoxin-induced muscle injury was found to enhance muscle regeneration by inducing myogenic gene expression and downregulating myostatin expression. Furthermore, this extract reduced nitrotyrosine protein levels and atrophy-related gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Furthermore, an investigation of the protein-protein interaction between FMOD and MSTN showed that FMOD decreases MSTN sensitivity to activin type IIB receptor (ACVRIIB, MSTN receptor) binding affinity [71]. Recently, we reported that Glycyrrhiza uralensis (a medicinal herb) inhibits MSTN expression and promotes myogenesis [76].…”
Section: Myostatinmentioning
confidence: 99%
“…Furthermore, an investigation of the protein-protein interaction between FMOD and MSTN showed that FMOD decreases MSTN sensitivity to activin type IIB receptor (ACVRIIB, MSTN receptor) binding affinity [71]. Recently, we reported that Glycyrrhiza uralensis (a medicinal herb) inhibits MSTN expression and promotes myogenesis [76].…”
Section: Myostatinmentioning
confidence: 99%
“…Nature is a plentiful source of medicinal herbs, and several natural foods that contain bioactive components with health benefits are commonly used as herbal remedies for many life-threatening diseases [ 71 , 72 , 73 ]. Herbal remedies offered a valuable resource for pharmacological agents for diabetes even before insulin and other pharmacological drugs were discovered, and have become an increasingly important aspect of searches for curative and adjunctive treatments [ 74 ].…”
Section: Ddp-4 Inhibitors From Natural Sourcesmentioning
confidence: 99%
“…Medicinal herbs have become increasingly important in the quest for more effective and adjunctive treatments [ 86 89 ]. Various pharmacological studies have reported that the active components of herbal medicines show therapeutic benefits in NDs via different mechanisms such as by increasing neurogenic activity, inhibiting cholinesterase activity, and controlling A β , tau, and α -synuclein metabolism by targeting autophagy [ 90 92 ].…”
Section: Beneficial Effects Of Medicinal Plants On Nds By Targeting Autophagymentioning
confidence: 99%
“…Medicinal herbs have become increasingly important in the quest for more effective and adjunctive treatments [86][87][88][89].…”
Section: Beneficial Effects Of Medicinal Plants On Nds By Targeting Autophagymentioning
confidence: 99%